Pleocytosis is not fully responsible for low CSF glucose in meningitis. Issue 1 (January 2018) - Baud, Maxime O.; Vitt, Jeffrey R.; Robbins, Nathaniel M.; Wabl, Rafael; Wilson, Michael R.; Chow, Felicia C.; Gelfand, Jeffrey M.; Josephson, S. Andrew; Miller, Steve
Abstract : Objective: The mechanism of hypoglycorrhachia—low CSF glucose—in meningitis remains unknown. We sought to evaluate the relative contribution of CSF inflammation vs microorganisms (bacteria and fungi) in lowering CSF glucose levels. Methods: We retrospectively categorized CSF profiles into microbial and aseptic meningitis and analyzed CSF leukocyte count, glucose, and protein concentrations. We assessed the relationship between these markers using multivariate and stratified linear regression analysis for initial and repeated CSF sampling. We also calculated the receiver operating characteristics of CSF glucose and CSF-to-serum glucose ratios to presumptively diagnose microbial meningitis. Results: We found that increasing levels of CSF inflammation were associated with decreased CSF glucose levels in the microbial but not aseptic category. Moreover, elevated CSF protein levels correlated more strongly than the leukocyte count with low CSF glucose levels on initial ( R 2 = 36%, p < 0.001) and repeated CSF sampling ( R 2 = 46%, p < 0.001). Hypoglycorrhachia (<40 mg/dL) was observed in 50.1% of microbial cases, but only 9.6% of aseptic cases, most of which were neurosarcoidosis. Absolute CSF glucose and CSF-to-serum glucose ratios had similar low sensitivity and moderate-to-high specificity in diagnosing microbial meningitis at thresholds commonly used. Conclusions: The main driver of hypoglycorrhachia appears to be a combination of microbial meningitis with moderate to high degrees of CSF inflammation and proteins, suggesting that the presence of microorganisms capable of catabolizing glucose is a determinant of hypoglycorrhachia in meningitis. A major notable exception is neurosarcoidosis. Low CSF glucose and CSF-to-serum glucose ratios are useful markers for the diagnosis of microbial meningitis.